Serviço Social e cotas: desafios para a permanência dos estudantes no Instituto Federal do Rio Grande do Norte - Pinheiro, Carina Lilian Fernandes (2020)
Social Work is a profession that had a conservative historical origin, focused on serving the interests of the bourgeoisie and the organization of the capitalist productive base. In this work, a brief report was initially produced on the performance of the Social Worker inserted in the Professional and Technological Education, more precisely in the Federal Institute of Education, Science and Technology of Rio Grande do Norte (IFRN), especially dealing with his performance for the permanence of the students after the institution of the quota policy through the Laws nº 12.711/2012 and 13.409/2016. The challenges related to the permanence of students posts to Social Assistants in the post-quota policy context are the object of this study, which has the objective of precisely identifying and reflecting on the challenges and demands that are presented to the Social Service professional inserted in the IFRN in enabling the permanence of students after the implementation of the quota policy in the institution. Methodologically, in order to achieve these objectives, a bibliographical and documentary research was develop an analysis of the themes treated in the research using dialectical historical materialism as a method, as well as qualitative and quantitative empirical field research, with the Social Workers who experienced the period before and after the quotas, and therefore, knowing the institutional reality before the quotas may be able to identify and reflect on what has effectively changed after the quotas. The empirical research was conducted through a questionnaire with open and closed questions, developed in Google Forms and sent a link via institutional email. In the evaluation of the data extracted from the questionnaires of the 17 Social Workers participating in the research, as well as the bibliographic and documentary content studied, it was possible to perceive and understand several challenges that are presented to the category for the permanence of students after quotas, among them: the absence of a permanence policy associated with the quota policy, which deals only with access; the increasing demand in the number of students seeking the institution's student assistance programs and the lack of budgetary resources, which is on the agenda before the courts and contingencies made by the government, especially in this current ultraconservative and neoliberal political conjuncture. It was also inferred from the study that the quotas brought new demands to the IFRN Social Worker and made the category rethink its professional practice and the programs focused on student permanence in the institution. It was concluded that is necessary for the Social Worker to remain aligned with his ethical-political project thinking the permanence in facing these challenges through a broader view, beyond the student assistance programs, but understanding their limits and possibilities, especially in the current conjuncture.